Conspecific nest attendance behaviour of Common Eider (Somateria mollissima) in response to Polar Bear (Ursus maritimus) foraging activity: error or intent? - Simone, Cassandra A.B.; Geldart, Erica A.; Semeniuk, Christina A.D.; Love, Oliver P.; Gilchrist, H. Grant; Barnas, Andrew F. (The Canadian Field-Naturalist, 2022)
Common Eider (Somateria mollissima) is a colonial nesting sea duck with extremely high nest attendance rates. Although individuals take few recess breaks away from their nest to feed or preen, previous research has shown that some female eiders in dense nesting assemblages engage in conspecific nest attendance, spending short amounts of time incubating nests of other females. However, to the best of our knowledge, most observations of these behaviours occur during regular recess events, as opposed to instances where females flush from their nest in response to a foraging predator. Using drone videography on East Bay Island, northern Hudson Bay, Nunavut, Canada, we observed conspecific nest attendance behaviours in 11 eiders that flushed in response to a foraging Polar Bear (Ursus maritimus). Of the 11 birds attending to other nests, only two predation events were observed at the focal bird's nest (i.e., two attenders' own nests were predated). Of the nine nests that were attended to, we also only observed two predation events. Motivations behind these behaviours are unclear, but conspecific nest attendance may serve as a type of distraction display, whereby activity at another female's nest leads the predator away from the focal bird's nest. However, given that, on East Bay Island, eiders are known to nest in proximity to kin, distraction displays at nests of related individuals would incur fitness costs. General confusion on nest location or the concealment of closely related eggs are more likely explanations for these behaviours.